ARITMETIKA SOSIAL PADA METODE COURSE REVIEW HORAY (CRH) DENGAN YEL-YEL BAHASA DERMAYU, INGGRIS, DAN INDONESIA - Farid Gunadi; Aan Juhana Senjaya; Dwi Arnum (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2019)
This research aims to determine differences in social arithmetic learning outcomes based on yells variations in the CRH method. This research uses quantitative research methods. Based on the results of the study, a significant average difference was obtained in class VII social arithmetic learning outcomes, so that the researchers conducted further tests with Scheffe and the results: between variations in the Dermayu yells and English did not have significant differences, but between yell-yell variations speak English and Indonesian and between the Dermayu and Indonesian chants are experiencing significant differences.